PENGARUH FLEXIBLE WORKING ARRANGEMENT TERHADAP JOB PURSUIT INTEREST PADA GENERASI Z DI KOTA BANDUNG DENGAN JOB AUTONOMY SEBAGAI VARIABEL MODERASI - Lestari, Diva Nurul; Sari, Puteri Andika (PUBLISHER ABISATYA DINAMIKA ISWARA PUBLISHING, 2026)
This study aims to analyze the effect of Flexible Working Arrangement (FWA) on Job Pursuit Interest among Generation Z in Bandung City, with Job Autonomy as a moderating variable. The study highlights the role of work flexibility in shaping young people’s interest in seeking and applying for jobs amid the growth of the gig economy. A quantitative approach was employed using Partial Least Squares–Structural Equation Modeling (PLS-SEM) on data collected from 170 Generation Z respondents who were job seekers and final-year university students. The results indicate that Flexible Working Arrangement has a positive and significant effect on Job Pursuit Interest. Furthermore, Job Autonomy strengthens this relationship, particularly for individuals with higher levels of work autonomy. These findings emphasize the importance of integrating flexibility and autonomy into recruitment strategies to attract Generation Z talent and contribute to the development of Signaling Theory in the context of the modern labor market.